Entrepreneurial Activities in Cassava Flour Processing and Their Effect on Cooperatives Performance in Oyi Local Government Area of Anambra State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examines entrepreneurial activities of cassava flour process among agricultural cooperative members in Oyi Local Government Area, Anambra State. It assesses the benefits of entrepreneurial activities of cooperative members on business environment, to examine the influence of entrepreneurial activities of cooperative members on the profitability of members business in Oyi Local Government Area, Anambra State.  Primary data were collected through structured questionnaire from respondents using simple random sampling. Descriptive and inferential statistics were used in the study. The hypotheses formulated were tested using Chi-Square statistical test. The Probability value = P < 0.024 shows that the result of the chi-square statistics is significant. We therefore reject the null hypothesis and accept the alternate by concluding that entrepreneurial activities of cassava flour processing have significant effect on the cooperative members business environment in Oyi local government area, Anambra state. Cooperative business managers should develop a blueprint that will sensitize and drive  membership, diversify their product mix and consequent expansion of their business volume to compete favourably with investor oriented-firms for economic sustainability and Cooperative businesses should uphold the cultural norms of their location of business and engage in activities that promote concern for their host community to avoid effects of restiveness which has the capacity of closing down cooperative shops.
Keywords: Entrepreneurial activities; cassava flour; cooperatives; Oyi; Anambra State; Nigeria